See you at Harry's - Knowles, Johanna, 1970- (Candlewick Press, 2013)
Caught in the midst of a hectic home life, twelve-year-old Fern turns to her best friend, Ran, for support. When a sudden turn of events wrench her family apart, however, she realizes she will need more than Ran's calm, meditative teachings to make things right.